KCPR Archive tape: Suzy Swiss Cheese, 1971 - Xmas Play, 1971 - Sign On, 1972 - House O' Usher, 10/1972 - Sleepy Hollow, 1972 (1971)
Contents of a tape compiling 5 distinct programs, ca. 1971-1972. 4 of the 5 programs are radio plays, with "Suzy Swiss Cheese" a serial play, and "An Empty Gesture" an original KCPR production. [00:00:00] "Suzy Swiss Cheese episode," February 7, 1971 [00:10:48] Christmas Play, "An Empty Gesture", KCPR Holiday Play Productions, December 1971 [00:30:25] "An Empty Gesture" credits: written by Mary Graham Lund; directed by Russ Lash and Lou Stern; actors were Jenny Duboise, Jody Puentes, Gary Gardner, Sheryl Portermont, Craig Hines, Edel Bryant, Berner Wright, Lou Rinaldi, Claudia Galloway [00:31:20] Christmas carol medley outro[00:34:47] KCPR Sign On, 1972 [00:35:00] Intro by Woody Goulart, KCPR general manager, and Steve Stagnero [00:37:11] San Luis Obispo Story program preview[00:39:20] Testing 1-2-3 program preview [00:40:52] Talk to an Addict program review, a KEVC simulcast, presented by Vic Bremer [00:41:55] Sundays-by-Request program preview and Mission City Missionaries program preview [00:42:23] Call for DJs and other assistance[00:43:20] KCPR on Cue, an outtakes show [00:50:30] "House of Usher" radio play, October 31, 1972[01:03:30] "House of Usher" end credits [01:04:30] "Legend of Sleepy Hollow" radio play, 1972 [01:27:26] "Legend of Sleepy Hollow" end credits